2017
DOI: 10.1002/jso.24804
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term outcomes and risk factors for pancreatic fistula after pancreatic enucleation: A single‐center experience of 142 patients

Abstract: Enucleation is a safe and feasible procedure for benign or low-grade pancreatic neoplasms. The rate of clinical POPF is acceptable, and clinical POPF occurs more frequently in elderly patients (≥60 years of age), patients with cystic neoplasms, or patients with an episode of acute pancreatitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Furthermore, sensitivity analysis of high-volume studies (more than 20 enucleations and more than 4 per year) showed that in specialised centres, pancreatic enucleations can be performed with no increased risk of POPF. Enucleation has also been shown to have excellent short and long-term oncologic outcomes, with no increased risk of tumour recurrence 1112. This may be partly explained by the fact that most tumours resected by enucleation were benign or had low malignant potential to begin with.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, sensitivity analysis of high-volume studies (more than 20 enucleations and more than 4 per year) showed that in specialised centres, pancreatic enucleations can be performed with no increased risk of POPF. Enucleation has also been shown to have excellent short and long-term oncologic outcomes, with no increased risk of tumour recurrence 1112. This may be partly explained by the fact that most tumours resected by enucleation were benign or had low malignant potential to begin with.…”
Section: Discussionmentioning
confidence: 99%
“…In several published studies, pancreatic enucleation has shown to have good oncologic outcomes, with no increased risk of tumour recurrence. 15,16 In a meta-analysis of 22 retrospective studies, Huẗtner FJ et al showed how pancreatic enucleation is associated with reduced rates of pancreatic insufficiency, as well as shorter surgery time, lower blood loss, and shorter hospital stay. 17 This is because most of the tumours resected by enucleation were benign or had low malignant potential.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, the patient must be informed that EN is a “mini invasive” pancreatic procedure with the advantage of preserving pancreatic parenchyma but without a reduced risk of POPF and its associated morbidity. The risk factors of overall and severe POPF have already been studied: on the one hand, several factors, such as age [ 6 ], body mass index [ 10 ], distance to the main pancreatic duct [ 17 ], history of acute pancreatitis [ 6 ], and New York Heart Association class [ 14 ], were independently identified by a single publication each (Table 1 ); on the other hand, cystic morphology [ 6 , 11 ] and tumor location [ 9 , 10 , 13 ] were identified in at least two independent series (Table 1 ). Our study confirmed that tumor location (i.e., the corresponding EN area) was relevant to predict POPF, but we improved the precision of this result by delimiting a particular zone with a higher risk than the rest of the pancreatic parenchyma.…”
Section: Discussionmentioning
confidence: 99%
“…Parenchyma-sparing pancreatectomies were proposed as an alternative to standard pancreatectomy for noninvasive tumors to avoid pancreatic endocrine and exocrine insufficiencies [ 1 4 ]. In this manner, enucleation (EN) was first performed in the 1960s [ 5 ]; currently, neuroendocrine tumors (particularly insulinoma) and branch-duct intraductal papillary mucinous neoplasms (IPMNs) are the more frequent tumors resected by EN [ 6 15 ]. As EN induces parenchyma incision and, occasionally, deep pancreas opening, it exposes patients to postoperative pancreatic fistula (POPF) by unknown main pancreatic duct injury or weakening, especially if thermo-coagulation has been used too closely.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation